2020
DOI: 10.1128/jvi.01736-19
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4-Using HIV Strains Predominate in Naive and Central Memory CD4 + T Cells in People Living with HIV on Antiretroviral Therapy: Implications for How Latency Is Established and Maintained

Abstract: HIV can persist in people living with HIV (PLWH) on antiretroviral therapy (ART) in multiple CD4+ T cell subsets, including naive cells, central memory (CM) cells, transitional (TM) cells, and effector memory (EM) cells. Since these cells express different levels of the viral coreceptors CXCR4 and CCR5 on their surface, we sought to determine whether the HIV envelope protein (Env) was genotypically and phenotypically different between CD4+ T cell subsets isolated from PLWH on suppressive ART (n = 8). Single ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 49 publications
4
24
0
Order By: Relevance
“…Although studying 2 uniform populations of HIV-infected individuals may have resulted in stronger levels of significance when comparing the level of clonality and naive infection, our approach provided additional insights revealing a continuum of reservoir size, and coreceptor tropism. We clearly found that those individuals with larger and predominant CXCR4-tropic reservoirs had more naive infection, consistent with a prior study ( 42 ), and more diverse reservoirs. This finding is reasonable because CXCR4-tropic viruses can directly infect naive T cells.…”
Section: Discussionsupporting
confidence: 92%
“…Although studying 2 uniform populations of HIV-infected individuals may have resulted in stronger levels of significance when comparing the level of clonality and naive infection, our approach provided additional insights revealing a continuum of reservoir size, and coreceptor tropism. We clearly found that those individuals with larger and predominant CXCR4-tropic reservoirs had more naive infection, consistent with a prior study ( 42 ), and more diverse reservoirs. This finding is reasonable because CXCR4-tropic viruses can directly infect naive T cells.…”
Section: Discussionsupporting
confidence: 92%
“…HIV-1 persists in all subsets of memory CD4 + T cells, including the classic memory subsets (memory stem cells, central memory cells, transitional memory cells, and effector memory cells), and a variety of functional subsets (particularly T follicular helper cells, T regulatory cells, T helper 1 (Th1) cells, and Th17 cells). Although memory cells harbor the bulk of HIV proviral DNA during ART, naive cells can also contribute to HIV persistence (Roche et al, 2019;Venanzi Rullo et al, 2019). Cells that have intrinsic self-renewing capacity might prove to be the most recalcitrant source of virus during long-term ART.…”
Section: Characteristics Of Infected Cells In Blood and Tissue Cellular Reservoirsmentioning
confidence: 99%
“…When we analysed the percentage of infected cells per subset, we found EM cells were preferentially infected compared to other subsets. This preferential infection of EM cells is likely mediated through the higher expression of CCR5 on these cells [32,33,56]. However, while our data suggests that infection of different memory CD4 + T cell subsets is reliant on the level of CCR5 expression, we cannot rule out other factors known to contribute to viral tropism including enhanced CD4 usage or fusogenicity [57].…”
Section: Discussionmentioning
confidence: 70%